1998
DOI: 10.1097/00006123-199811000-00035
|View full text |Cite
|
Sign up to set email alerts
|

PCV Chemotherapy for Recurrent Oligodendrogliomas and Oligoastrocytomas

Abstract: These results suggest that chemotherapy with PCV is effective in the treatment of recurrent low-grade oligodendrogliomas and oligoastrocytomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(84 citation statements)
references
References 39 publications
1
80
0
3
Order By: Relevance
“…Since Cairncross and McDonald observed that recurrent anaplastic oligodendrogliomas respond to chemotherapy, 3 several groups have reported on the chemosensitivity of both high-and low-grade oligodendrogliomas and mixed oligoastrocytomas. [4][5][6][7] As a result oligodendrogliomas are increasingly being treated with chemotherapy, in contrast to, for example, astrocytomas, which are substantially more resistant to chemotherapeutic agents. [4][5][6][7] In general brain tumors are pathologically diagnosed by analysis of tumor tissue obtained (invasively) by biopsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Cairncross and McDonald observed that recurrent anaplastic oligodendrogliomas respond to chemotherapy, 3 several groups have reported on the chemosensitivity of both high-and low-grade oligodendrogliomas and mixed oligoastrocytomas. [4][5][6][7] As a result oligodendrogliomas are increasingly being treated with chemotherapy, in contrast to, for example, astrocytomas, which are substantially more resistant to chemotherapeutic agents. [4][5][6][7] In general brain tumors are pathologically diagnosed by analysis of tumor tissue obtained (invasively) by biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] As a result oligodendrogliomas are increasingly being treated with chemotherapy, in contrast to, for example, astrocytomas, which are substantially more resistant to chemotherapeutic agents. [4][5][6][7] In general brain tumors are pathologically diagnosed by analysis of tumor tissue obtained (invasively) by biopsy. Both magnetic resonance imaging (MRI) and 1 H magnetic resonance spectroscopy (MRS) have proven to be powerful noninvasive tools for the characterization of brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…5) PCV therapy is effective against both recurrent and newly diagnosed oligodendroglioma. 10,14) In our series, response to PMV therapy was observed in three patients with recurrent malignant oligodendroglial tumors previously treated by chemoradiation therapy. Three patients with recurrent tumor previously treated with radiation therapy also showed inhibition of tumor growth using PMV.…”
Section: Discussionmentioning
confidence: 62%
“…5,9) Responses to PCV have also been observed in both recurrent and newly diagnosed oligodendrogliomas with both low-grade and high-grade malignancy. 1,2,6,8,[10][11][12]14) The present study investigated the benefits and toxicity of combination chemotherapy (PMV) using procarbazine, ranimustine (MCNU), and vincristine, which is a replacement for PCV using agents available in Japan, in patients with both low-grade and high-grade oligodendrogliomas and oligoastrocytomas.…”
Section: Introductionmentioning
confidence: 99%
“…12) Although no consensus on the routine use of chemotherapy in treating LGG, and especially astrocytomas, has been reached yet, its efficacy has been demonstrated in terms of clinical and radiological response either as initial treatment [2][3][4]8,10,13,15,24,27) or as salvage therapy after surgery and radiotherapy. 17,18,22,23,26,27) Complete neuroradiological disappearance of a tumor is infrequent, so good response is defined as volumetric regression or stabilization over time. Since progression of LGG towards highergrade malignancies has been associated with the accumulation of genetic abnormalities, 19,29) the difference in response to chemotherapy among histologically similar tumors is probably due to the heterogeneity in the genetic pattern of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%